Supply Chain Management - Rojek Kinga (My University, 2006)
From the point of view of the international business, it is easy to notice that the transformation of the market of producer to market of customer led to changes in the market conditions in which the potential enterprise has to manufacture and sell its products and services. It is not to contradict that most of the market conditions are dictated by globalization. The issue of progressive globalization works with the shortage of product life cycle, increasing demand on the up-market products and consequently leads to emerge the market in which the rules are defined by customer. In this situation the producer is obliged to deepen its knowledge about the customer’s desires and wishes and also to forecast the future demand and consumers' behaves in the market. With the changes in the market also the traditional definition of logistics is still changing. At the beginning logistics was only a part of production function, now it is the crucial element of the value chain in the company, which can decide about the success or failure in the market. This thesis was composed during the author’s half-year internship in logistic department of Valeo Klimasysteme in Bad Rodach (Germany) which is one of the most popular producers of cooling systems for cars. The main partners of this company are Daimler Chrysler, BMW, Volkswagen, Saab, Volvo and Ford. The observation of daily business was an inspiration for the author to write this thesis. The structure of this paper is not accidental; it is just the answer to the questions and solution to problems with which she had to deal with. The reader can find here the combination of the theoretical and practical knowledge of her co-workers. Working for Valeo was a big challenge and opportunity to experience how the logistic department of the international concern cooperates with companies which are located in such countries as United Stated, Great Britain, Mexico, Brazil, China, Turkey, Africa and many more.
Zarządzanie w logistyce
Keywords: logistics; supply chain management; production planning system; master scheduling; material requirements planning; capacity management; inventory control policy; kanban; warehouse operations